Y- CHROMOSOMAL MICRODELETIONS IN A LOCAL INFERTILE MALE POPULATION OF PAKISTAN - Siddique, Ayesha; Qureshi, Hamid Javaid; Siddique, Saqib; Husnain, Afia (Pakistan Journal of Physiology, 2009)
Background: The aim of this study was to determine occurrence, frequency and pattern of microdeletions of the long arm of Y chromosome within the AZFa, AZFb, and AZFc subregions in patients with idiopathic azoospermia, and correlate the microdeletions with clinical phenotypes to determine the most important subregion for screening in a sample of local population of Pakistan. Methods: The patients were selected from the Male Infertility Clinic, Services Hospital, Lahore. They included 53 cases, 25-45 years of age with male factor infertility and 53 age matched controls with normal semen parameters. Blood and semen samples were obtained from all the participants. We performed semen analysis, polymerase chain amplification of 8 DNA loci on the long arm of the Y chromosome using 8 pairs of primers according to guidelines by the European Academy of Andrology. Plasma FSH and testosterone levels were also determined to assess the endocrine status. Results: No Y-chromosomal microdeletion could be detected in the infertile or fertile males included in the study. One of the two samples of EAA Quality Control Schemes showed deletion in AZFc region and all the three (AZFa, AZFb, AZFc) were missing in the second sample. Mean serum concentrations of FSH and testosterone in both groups of subjects were found to be within the normal range. However, FSH levels were significantly higher in infertile males than the fertile males whereas testosterone levels were significantly lower in infertile men as compared to fertile subjects. Conclusion: These results suggest a much lower Yq deletion frequency than previously thought, even among strictly selected patients with idiopathic azoospermia or oligozoospermia in a sample of local population of Pakistan.